Cheilitis Granulomatosis - A Case Discussion - Karthikeya Patil; Mahima V Guledgud; Prasannasrinivas Deshpande; Nagabhushana Doggalli; Mounika Prashanthi N (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Cheilitis granulomatosa is an idiopathic, cosmetically unpleasant, non-specific, painless,persistent granulomatous inflammation which affects one or both the lips. It is considered under the entityorofacial granulomatosis with very high rate of recurrence inspite of good treatment.Presentation of case: A 45 years old female patient reported with the chief complaint of swelling in theupper and lower lips for 2 years which had gradually increased in size since the onset. The swelling wasasymptomatic, firm in consistency. On histopathological examination the condition was diagnosed ascheilitis granulomatosaDiscussion: Cheilitis granulomatosa is considered as an entity of orofacial granulomatosis. It is asymptomatic,persistent swelling of the lips. The primary goal of management should be elimination of the predisposingfactor. Intralesional corticosteroids are considered as gold standard in the management of conditions. Insevere cases surgical management is helpful.